What does lung function tell us about respiratory multimorbidity in childhood and early adulthood? Results from the MAS birth cohort study. Issue 5 (7th May 2018) - Schramm, Dirk; Reuter, Marvin; Grabenhenrich, Linus B.; Schuster, Antje; Lex, Christiane; Bauer, Carl‐Peter; Hoffmann, Ute; Forster, Johannes; Zepp, Fred; Bergmann, Renate L.; Bergmann, Karl E.; Wahn, Ulrich; et al.
Abstract: Background: Interaction between respiratory multimorbidity and lung function has not been examined in longitudinal population studies. We aimed to assess the association of multimorbidity of asthma and rhinitis with lung function and bronchial hyperresponsiveness in comparison with single and no allergies from early school age to young adulthood. Methods: In 1990, the Multicenter Allergy Study birth cohort recruited 1314 newborns from 5 German cities. At 7, 13, and 20 years, we performed lung function and bronchial challenge tests. We assessed symptoms, medications, and doctor's diagnoses for asthma and rhinitis for 3 outcomes: current multimorbidity (both coexisting), asthma only, and rhinitis only. Results: From 7 to 20 years, multimorbidity prevalence more than doubled from 3.5% to 7.7%, current asthma only (without rhinitis co‐occurring) decreased by half from 2.8% to 1.3%, and current rhinitis only (without asthma co‐occurring) increased from 14.3% to 41.6%. Resting lung function parameters differed between allergic and asymptomatic participants but showed no considerable differences between the allergic phenotypes. Frequency and severity of bronchial hyperresponsiveness were particularly associated with multimorbidity. At the age of 20 years, participants with multimorbidity showed a clearly higher severity in hyperresponsiveness compared to participants who suffered only asthma ( P  = .049) or rhinitis ( P  = .008) or were asymptomatic ( P  < .001). Conclusion: Single lung function measurements from childhood ongoing do not seem to discriminate between subjects with multimorbidity, single allergies, and no allergy. Our results show that multimorbidity is associated with more severe symptoms compared to those suffering only a single allergic disease. Abstract :